Pengaruh Inflasi, Bi Rate, Nilai Tukar, dan Penghimpunan Dana Pihak Ketiga Terhadap Penyaluran Kredit pada Perbankan LQ45 - Greza Agrestya Arviandy; Merry Susanti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This research aims to analyze the effect of inflation, the BI interest rate (BI Rate), exchange rate, and third-party funds on credit distribution in the banking sector in Indonesia. This research uses a quantitative approach using secondary data obtained from companies’ annual financial reports, official publications of Bank Indonesia, and the Central Statistics Agency (BPS) during the 2022–2025 research period. The sample used in this research was determined using a purposive sampling technique, resulting in five banks consistently listed in the LQ45 index during the research period. The analytical method used in this study is multiple linear regression analysis with the assistance of Statistical Product and Service Solutions 31 (SPSS 31) software. The results show that inflation, BI Rate, and exchange rate have no significant effect on credit distribution, while third-party funds have a positive and significant effect on credit distribution. These findings indicate that internal factors, particularly the collection of third-party funds, have a stronger influence on credit distribution activities compared to macroeconomic factors.